2017
DOI: 10.1007/978-3-319-57732-6_23
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Hemostatic Disorders: SOCE and Ca2+ Handling in Platelet Dysfunction

Abstract: Among the Ca entry mechanisms in platelets, store-operated Ca entry (SOCE) plays a prominent role as it is necessary to achieve full activation of platelet functions and replenish intracellular Ca stores. In platelets, as in other non-excitable cells, SOCE has been reported to involve the activation of plasma membrane channels by the ER Ca sensor STIM1. Despite electrophysiological studies are not possible in human platelets, indirect analyses have revealed that the Ca-permeable channels involve Orai1 and, mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 143 publications
0
5
0
Order By: Relevance
“…TRPC6 −/− mice have reduced or absent Ca 2+ entry upon stimulation with 1-oleoyl-acetyl-sn-glycerol (OAG) [201,202]. Studies have demonstrated involvement of TRPC6 in both SOCE [203] and SOCE-independent [204,205] Ca 2+ mobilisation. Although increasing evidence links TRP channel defects to cardiovascular and haemostatic pathology (reviewed in [206]), more work is required in order to understand associations with immunological or inflammatory conditions.…”
Section: Monocytes and Macrophagesmentioning
confidence: 99%
“…TRPC6 −/− mice have reduced or absent Ca 2+ entry upon stimulation with 1-oleoyl-acetyl-sn-glycerol (OAG) [201,202]. Studies have demonstrated involvement of TRPC6 in both SOCE [203] and SOCE-independent [204,205] Ca 2+ mobilisation. Although increasing evidence links TRP channel defects to cardiovascular and haemostatic pathology (reviewed in [206]), more work is required in order to understand associations with immunological or inflammatory conditions.…”
Section: Monocytes and Macrophagesmentioning
confidence: 99%
“…In 1990 Kwan and colleagues demonstrated that the refilling process does not involve a direct route to the intracellular stores, but it is the result of a sequential Ca 2+ transport into the cytoplasm and the subsequent uptake from the stores by Sarco/Endoplasmic Reticulum Ca 2+ -ATPase (SERCA) (Kwan et al, 1990 ). Subsequently, SOCE has been characterized and widely studied in non-excitable cell types (Tojyo et al, 2014 ; Verkhratsky and Parpura, 2014 ; Lopez et al, 2017 ), while its role in excitable cells was difficult to demonstrate. However, few years before the first formulation of Putney's model (Putney, 1986 ), Casteels and Droogmans reported similar observations in Vascular Smooth Muscle Cells (VSMCs) (Casteels and Droogmans, 1981 ).…”
Section: General Overview Of Store-operated Ca 2+ mentioning
confidence: 99%
“…STIM1 and Orai1 are regulated by the serum/ glucocorticoid-regulated protein kinase 1 (SGK1) (Lang, Eylenstein, Shumilina, 2012). Acting upstream of the STIM1-Orai1 pathway, SGK1 is considered a potent regulator of platelet function (Lopez, Salido, Rosado, 2017;Lang et al, 2013). Ligustrazine, which chemical name is tetramethylpyrazine (TMPZ), is an active constituent of Rhizoma ligusticum that is frequently used in traditional Chinese medicine to prevent the onset or delay the progression of cardiovascular diseases (Guo, Liu, Shi, 2016;Qian et al, 2014;Zhao, Liu, Chen, 2016).…”
Section: Introductionmentioning
confidence: 99%